Cognitive Investments in Academic Success: The Role of Need for Cognition at University - Grass, Julia; Strobel, Alexander; Strobel, Anja (Frontiers in Psychology, 2017)
Previous research has shown that Need for Cognition (NFC), the individual tendency to engage in and enjoy cognitive endeavors, contributes to academic performance. Most studies on NFC and related constructs have thereby focused on grades to capture tertiary academic success. This study aimed at a more comprehensive approach on NFC's meaning to success in university. We examined not only performance but also rather affective indicators of success. The current sample consisted of 396 students of different subjects with a mean age of 24 years (139 male). All participants took part in an online survey that assessed NFC together with school performance and further personality variables via self-report. Success in university was comprehensively operationalized including performance, satisfaction with one's studies, and thoughts about quitting/changing one's major as indicators. The value of NFC in predicting tertiary academic success was examined with correlation analyses and path analysis. NFC significantly correlated with all success variables with the highest correlation for study satisfaction. Path analysis confirmed the importance of NFC for study satisfaction showing that NFC had a significant direct effect on study satisfaction and via this variable also a significant indirect effect on termination thoughts. This study clearly indicates that NFC broadly contributes to the mastery of academic requirements and that it is worthwhile to intensify research on NFC in the context of tertiary education.